2001
DOI: 10.1046/j.1440-1770.2001.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Trophic state, fish community and intensive production of salmonids in Alicura Reservoir (Patagonia, Argentina)

Abstract: The Governments of the Provinces located in Patagonia, Argentina, promote the intensive breeding of salmonids in the Andean Patagonian region. Although annual production is low (450 ton ha–1 year–1), some effects are significant. Waste produced by salmonid breeding (feed losses, faeces and excretion) increases nutrient and organic matter concentrations, which cause modifications of water quality, sediments and biota. A consequent risk is the elevation of eutrophication levels. Possible changes in water composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 11 publications
3
19
0
6
Order By: Relevance
“…In this study, our finding suggesting that the total organic substance values at the cage stations (7.02-7.77 %) showed an increase with respect to those at the control stations seems to coincide with the results of different research (Jiwyam and Chareontesprasit, 2001;Temporetti et al, 2001;Alpaslan and Pulatsü, 2008;Rooney and Podemski, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, our finding suggesting that the total organic substance values at the cage stations (7.02-7.77 %) showed an increase with respect to those at the control stations seems to coincide with the results of different research (Jiwyam and Chareontesprasit, 2001;Temporetti et al, 2001;Alpaslan and Pulatsü, 2008;Rooney and Podemski, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Wild and farmed rainbow trout were identified according to their external characteristics (Temporetti et al, 2001;Fiske et al, 2005). However, since previous studies in Chilean Patagonia have found that ERTand WRTcan exhibit no obvious phenotypic differences (Consuegra et al, 2011), estimated abundances of ERT in the present study are probably underestimated (conversely, diet overlap between ERT and WRT may be overestimated).…”
Section: Methodsmentioning
confidence: 57%
“…Considering that the abundance and growth of Daphnia in Patagonian lakes is limited mainly by phosphorous (Balseiro et al, 2007), our fish stomach content data suggest an increase in the availability of this crustacean in the Alicurá reservoir, which may be a delayed consequence of nutrient discharges from aquaculture activities (Temporetti et al, 2001).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The effect on the sediment of a cage culture with a production capacity of 450 t•y −1 (cage production started in 1986) in Alicura Reservoir was examined by [21]. Comparing sediment TP and TN concentrations, the increase in TP was found to be higher than TN, similar to [20].…”
Section: Discussionmentioning
confidence: 99%